STUDI KETERLAMBATAN PENYELESAIAN SKRIPSI MAHASISWA PROGRAM STUDI PENDIDIKAN TATA RIAS DAN KECANTIKAN JURUSAN TATA RIAS DAN KECANTIKAN FAKULTAS PARIWISATA DAN PERHOTELAN - Annisa, Sri Willy; Rahmiati, Rahmiati; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The goal of this research is to discover the difficulties that are experienced by the college students to accomplish the thesis in study program of Make-up and Beauty Education majoring in TRK-FPP-UNP. There are two focuses of this research, they are:1) the internal factor : college students difficulty in finding the problem/idea that will be studied in writing the thesis, and their difficulty in presenting the idea and concept in the background of the problem. 2) the external factor: the difficulty in collecting the information of the data in the field, and their difficulty in doing some related consultation in communicating with the advisor. This is a qualitative research.The data collecting technique in this research uses observation, interview, and documentation method. The validity technique is completed by doing observation extension, observation exertion, triangulation, and auditing. The result of this research shows that the college students experience difficulties in finding the problem/idea that will be studied in writing the thesis; The difficulty of these college students in presenting the idea in background of the problem; The difficulty in collecting the data; and inappropriate communication technique used by the college students. From the research results can be recommended for students to have an interest in reading and motivation in working on the thesis as well as establish a good relationship with the advisor so that the counseling process can proceed smoothly.Keywords: study delays, the completion of the thesis, study program of Make-up and Beauty Education.